Optimization of Employee Workload to Achieve Effectiveness of Man Power Planning at PT. SPINDO Depo Samarinda - Setya Budi; Boy Isma Putra; Athika Sidhi Cahyana; Indah Apriliana Sari W (Universitas Muhammadiyah Sidoarjo, 2021)
Intense competition in today's industrial world requires companies to keep abreast of developments. The more years, higher the need for labor costs. To reduce high production costs, one step is to cut existing labor. By cutting the number of workers, the workload that will be borne by workers will also increase. PT. SPINDO, is a manufacturing company engaged in the production of the steel pipe industry. To expand market reach, a breakthrough was made to open a new depot located in the city of Samarinda. At the beginning of the opening along with the Covid-19 outbreak, market demand was minimal. The impact on the work load in the depot is also low. The Full Time Equivalent method is a calculation process that uses working time as a reference in determining workload. In this research, the workload value most of the employees at PT. SPINDO Depo Samarinda is included in the underload category. So that man power planning is needed by cutting the number of existing employees to balance work load and the number of manpower. After the manpower planning was carried out, the work load that was previously unbalanced was balanced because the workload had been distributed to the employees.